PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVC SEKOLAH DASAR NEGERI 108 PEKANBARU - Lazim N; Zulkifli Zulkifli; Rima Rima (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
The problem on this research was that the low score of students’ learning on social science study. There werestill a lot of students that did not understand basic concepts and tended to memorize examples. It was showed by58,07% from 31 students achieving minimum criteria completeness (KKM) from students’ test score in IVCclass of SDN 108 Pekanbaru for Koperasi subject. The students’ average score was 62,4, and the KKM stated byschool was 68. Based on this problem it was needed to do an action research using cooperative learning modelsTeams Games Tournaments (TGT) type. This research aims to know whether the implementation of cooperativelearning models Teams Games Tournaments (TGT) type can improve students’ social science learningoutcomes at IVC class of SDN 108 Pekanbaru in 2013/2014 with 31students. This research was done in twocycles. First cycle consists of three meetings with one daily test and first tournament, and cycle II consists ofthree meetings with one daily test and second tournament. Instruments to collect data in this research areteacher’s observation sheets, students’ observation sheet, and tests. By implementing using cooperative learningmodels Teams Games Tournaments (TGT) type can improve students’ mathematics learning outcomes.Percentage of completeness in basic score was 54,8% (62,40 in average), and it changed into 77,4% (75,6 inaverage) in cycle I and 87,1% (81,1 in average) in cycle II. Percentage of teacher’ activity in cycle I was 81,9%and 92,3% in cycle II. Then percentage of students’ activity in cycle I was 75,4% and 92,2% in cycle II. Fromthose data it proves that the implementation of cooperative learning models Teams Games Tournaments (TGT)type can improve students’ learning outcomes at IVC class of SDN 108 Pekanbaru.Key Words : cooperative teaching and learning model, Teams Games Tournaments (TGT),learning outcomes